ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN VIRTUAL REALITY (VR) PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 1 SUNGAI RAYA - Irfan, Muhammad Rifai; Purwaningsih, Endang; Basri, Muhammad (Jurnal Edukasi Ekonomi, 2024)
As educators, teachers should be ready to face the rapid development of technology. Teachers need to develop technology-based learning media to create a different learning atmosphere than usual so that it can affect the increase in motivation and learning outcomes of students. The purpose of this study was to analyze the needs of students on Virtual Reality (VR) based learning media in the economics class X SMA Negeri 1 Sungai Raya. The research method used is a qualitative research method. The research data used are the results of observations, teacher interviews, and student interviews to find out the needs of Virtual Reality (VR) learning media. The results of this study indicate that the need for virtual reality (VR) based learning media is needed to support the learning process. The development of virtual reality-based learning media must be tailored to the interests and interests of students in online games.